Exploring the Reasons for Seeking Orthodontic Treatment among the Patients Attended in Selected Private Settings - Md Golam Rubby; Nihar Sultana; Abdullah Al Mamun; Fatema Jannath (Update Dental College, 2023)
Aim : This study was conducted to explore the reasons and influential factors for seeking orthodontic treatment among the orthodontic patients. Methods : A total 126 patients were interviewed for the duration of four months with a semi structured questionnaire who attended at two private dental settings in Dhaka and Jeshore city. In depth interview was conducted with some patients with their guardian to explore the influential factors for seeking orthodontic treatment. Results : The study result showed out of 126 patients majority 82.5% were female, the mean age of the patient was 17.9(±5.9) years with range 7-36 years. Social harassment like teasing or bullying experiences was the influential factor for seeking orthodontic treatment mentioned by majority orthodontic treatment seeker. Other influential factors noted as desire to have better facial or aesthetic appearance, better career opportunity. Conclusion : Present study concluded that patients seek orthodontic treatment mainly due to psychosocial reason like to get rid of social harassment, also to improve their dental appearance and aesthetic.    Update Dent. Coll. j: 2023; 13(1): 14-16